Investigation of the playing digital games on shoulder flexibility, muscle strength and reaction speed in volleyball players - Güney, Şeyma; Şahin, Fatma Neşe; Arslanoğlu, Cansel; Güler, Özkan; Aydoğmuş, Mert; Doğan, Abdullah; Ayyıldız Durhan, Tebessüm; Arıkan, Gökhan; Yaşar, Onur Mutlu; Küçük, Hamza (Frontiers in Public Health, 2024)
Esports is a natural extension of digital games. Digital games provide a platform for players to showcase their skills, thereby forming the foundation of esports. These two domains continuously support each other, demonstrating significant growth in popularity and establishing a solid presence in the competitive landscape. Digital games require high levels of attention, strategy, reflexes, and coordination, offering pathways to reach the pinnacle of competition. This study investigates the effects of digital gaming on the physical performance, shoulder flexibility, muscle strength and reaction speed of female volleyball players. A total of 50 female volleyball players took part, who were divided into two groups based on their digital playing habits: Group 1 consisted of female players who played video games for at least 4 hours per day in the last six months, while Group 2 included those who played less than 4 hours per day. In the study, the Activ5© Handheld Digital Dynamometer was used to measure the strength of the shoulder muscles during various movements, including flexion, hyperextension, abduction, internal rotation and external rotation. In addition, the BlazePod™ trainer device was used to assess reaction times. The results showed that volleyball players who frequently played digitally showed significant improvements in shoulder flexibility, especially in flexion of the non-dominant side. In addition, these players showed faster reaction times than those who played less frequently. However, a significant decrease in hyperextension muscle strength was observed in the group that frequently played digital games. The study highlights that while digital games can improve certain physical skills such as reaction speed and shoulder flexibility, they can also contribute to muscular imbalances or a decrease in muscle strength in certain areas. These findings suggest potential benefits for volleyball players, particularly in movements that require quick reflexes and flexibility, such as serving and spiking. However, the results also raise concerns about potential negative effects on muscle strength and posture, highlighting the need for balanced training programs to mitigate these effects. Further research is needed to investigate the long-term effects of digital games on athletic performance and physical health.